The system of concentration camps in the cities of the Smolensk province during the Soviet-Polish war of 1919–1921 - Gavrilenkov, Aleksey (City and War, 2021)
The creation of concentration camps in Soviet Russia began in 1919. Along with criminals, Polish prisoners of war, civilian prisoners, and hostages were held in concentration camps. In the future, the Soviet state moved away from this practice – Polish prisoners were placed in separate concentration camps. Several concentration camps were established in the Smolensk province during the civil war. However, two of them, in the cities of Smolensk and Roslavl, contained Polish prisoners. Concentration camps were located in the Central parts of cities. To ensure the viability of the concentration camps, it was necessary to cooperate with Soviet institutions in both Smolensk and Roslavl. The activities of the concentration camps were closely linked to the County and provincial Executive committees, as they were under the control of these Executive committees. Provincial or County Executive authorities made decisions on various issues related to the activities of concentration camps where Polish prisoners of war, hostages, and Polish civilians were held.